Menjembatani Warisan Klasik ke Ranah Lokal: Analisis Transmisi ‘Ulūm al-Qur’ān Pesantren Kitab al-Iksīr Karya K.H. Bisri Musthofa - Itmam Muhammad (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This study examines al-Iksīr fī Tarjamah Naẓam ʿIlmi at-Tafsīr by K.H. Bisri Musthofa as a key locus of Qur’anic sciences (‘ulūm al-Qur’ān) transmission within Indonesian pesantren. Addressing the gap left by scholarship that privileges Bisri’s al-Ibrīz, the research employs a qualitative–philological design: (1) collation of the 1960 printed manuscript, (2) structural mapping of its six-chapter framework, and (3) intertextual comparison with eleven classical sources, foremost al-Suyūṭī’s ‘Ilmu al-Tafsīr and al-Itqān. Three principal findings emerge. First, while al-Iksīr reproduces al-Zamzamī’s Manẓūmah, it supplements the nadhm with contextual taʿlīq, tanbīḥāt, and faʾidāt that elucidate tajwīd, sanad, and abrogation for Javanese students. Second, its use of Javanese-Pegon script and the makna gandul glossing system demonstrates pesantren vernacularisation strategies, bridging Arabic textual authority with local audiences. Third, Bisri’s knowledge genealogy—rooted in Sholeh Darat, Mahfudz Termas, and Sayyid ʿAlwī al-Mālikī—confirms the work’s academic validity through a dual (local–Hijaz) sanad. These findings refine the historiography of Indonesian ‘ulūm al-Qur’ān by positioning pesantren as active producers of tafsīr literature. The study recommends integrating pesantren manuscripts into university curricula and future Qur’anic-studies research agendas.